2016
DOI: 10.1021/acs.jpcc.6b08182
|View full text |Cite
|
Sign up to set email alerts
|

Is the Imidazolium Cation a Unique Promoter for Electrocatalytic Reduction of Carbon Dioxide?

Abstract: There has been considerable recent interest in the use of the imidazolium cation as a promoter in the heterogeneous and homogeneous electrocatalysis of CO2 reduction. However, despite its widespread use for this purpose, the mechanism by which imidazolium operates is not yet fully established. The present work reveals that enhanced catalytic activity is achieved by addition of many cations other than imidazolium. Under cyclic voltammetric conditions at a Ag electrode in acetonitrile solutions (0.1 M n-Bu4NPF6)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
133
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 115 publications
(146 citation statements)
references
References 40 publications
11
133
2
Order By: Relevance
“…These authors proposed thatt he IL decreases the energy of the CO 2 C À radical intermediate, most likely through complexation. Zhao et al [20] demonstrated that the features highlighted above are not unique to imidazolium cations, and many other organic cations can produce the same effects. [18] Furthermore, Rosenthale tal.…”
Section: Introductionmentioning
confidence: 99%
“…These authors proposed thatt he IL decreases the energy of the CO 2 C À radical intermediate, most likely through complexation. Zhao et al [20] demonstrated that the features highlighted above are not unique to imidazolium cations, and many other organic cations can produce the same effects. [18] Furthermore, Rosenthale tal.…”
Section: Introductionmentioning
confidence: 99%
“…IL cations catalyze CO 2 RR . Although there is no consensus on the co‐catalytic mechanism, it was shown that imidazolium cations directly acted as co‐catalysts stabilizing a CO 2 RR intermediate, whereas the other cations, such as pyrrolidinium, activate CO 2 RR by modifying the electrical double layer . Both cations and anions determine the electrical double layer composition and structure at an IL/electrode interface and, thus, may affect CO 2 RR.…”
Section: Methodsmentioning
confidence: 99%
“…The addition of ionic liquids (ILs) to electrolytes significantly decreases the onset potential for the CO 2 RR and helps to suppress HER . ILs based on imidazolium, pyrrolidinium, and pyrazolium cations were found to be efficient cocatalysts. However, the high cost of ILs and their high viscosity hamper their direct application in the CO 2 RR.…”
Section: Figurementioning
confidence: 99%